Ab Externo Scleral-Fixated Intraocular Lens As A Management in Aphakic Eye: Poster Presentation - Case Report - Resident - Budiman; Sudjana, Briska; Knoch, Andrew M.H.; Sugiarti, Emmy Dwi; Melino, Ludwig (Majalah Oftalmologi Indonesia, 2023)
Introduction : Varied technique of secondary intraocular lens (IOL) implantation are exist. Scleral-fixated IOL implantation become popular both with or without sutures. The one of sutures technique is ab externo Case Illustration : A 68 year old man came with blurry vision on left eye (LE) since one month ago. He had history of primary angle closure suspect and posterior subcapsular cataract on LE and managed with Intracapsular Cataract Extraction in January 2021. Ophthalmology examination of LE revealed uncorrected visual acuity (UCVA) 1/60, irregular updrawn pupil with diameter 7.4mm x 5.3 mm, and aphakic lens. The best corrected visual acuity (BCVA) with S+12.00 C-0.75 x 80 was 0.4f. The patient underwent secondary IOL by using 3 pieces IOL with ab externo scleral- fixated on his left eye (Figure 1). Power IOL determined was +24.00 diopter with target of refraction was emmetropia. One day postoperatively, the UCVA was 0.08 pinhole 0.125 with good centration of scleral fixation IOL. First month postoperatively, BCVA with S-1.75 C-1.00 x 50 was 0.4 on snellen chart. Discussion : Aphakia with inadequate capsular support can be seen in several conditions. Technique of introducing two suture loops for scleral fixation of an IOL by ab externo procedure, which proved safe and effective. Scleral fixation of IOL in the posterior chamber, although technically demanding, allows good visual outcomes. Conclusion : Ab externo scleral-fixated IOL implantation is an effective rescue procedure for eyes with deficient capsular support.